Identification of the human PMR1 mRNA endonuclease as an alternatively processed product of the gene for peroxidasin-like protein - Gu, Shan-Qing (Cold Spring Harbor Laboratory Press, 2012)
The PMR1 endonuclease was discovered in Xenopus liver and identified as a member of the large and diverse peroxidase gene family. The peroxidase genes arose from multiple duplication and rearrangement events, and their high degree of sequence similarity confounded attempts to identify human PMR1. The functioning of PMR1 in mRNA decay depends on the phosphorylation of a tyrosine in the C-terminal polysome targeting domain by c-Src. The sequences of regions that are required for c-Src binding and phosphorylation of Xenopus PMR1 were used to inform a bioinformatics search that identified two related genes as potential candidates for human PMR1: peroxidasin homolog (PXDN) and peroxidasin homolog-like (PXDNL) protein. Although each of these genes is predicted to encode a large, multidomain membrane-bound peroxidase, alternative splicing of PXDNL pre-mRNA yields a transcript whose predicted product is a 57-kDa protein with 42% sequence identity to Xenopus PMR1. Results presented here confirm the existence of the predicted 57-kDa protein, show this is the only form of PXDNL detected in any of the human cell lines examined, and confirm its identity as human PMR1. Like the Xenopus protein, human PMR1 binds to c-Src, is tyrosine phosphorylated, sediments on polysomes, and catalyzes the selective decay of a PMR1 substrate mRNA. Importantly, the expression of human PMR1 stimulates cell motility in a manner similar to that of the Xenopus PMR1 expressed in human cells, thus providing definitive evidence linking endonuclease decay to the regulation of cell motility.